Digital health implementation guide for the Pacific. (Asian Development Bank, 2021)
With increased internet connectivity, Pacific island countries have more opportunities to connect remote health facilities for greater information exchange. This guide draws on experiences from Pacific island countries that have already invested in digital health and brings together practical tools and resources to support all stages of digital health planning and implementation. It includes extensive contributions from practitioners, government staff, and development partners in the Pacific health sector.